Understanding youth experiences in Mitchells Plain: a narrative photovoice investigation - Marishane, Mokgadi (Department of Psychology, 2025)
South African young people in townships such as Mitchells Plain live lives marked by continuity and change and plagued by violence or the threat of it. Research with youth has historically focussed on educational attainment, employment, and risk factors for disease. Such scholarship, which is frequently decontextualised, offers limited insights into how adolescents' identities are formed in response to the broader communities they live in. This paper aimed to broaden the scope of research around identity development in adolescent youth by utilising decolonial feminist approaches and photovoice methods in a secondary research study to investigate how youth in Mitchells Plain define themselves and their communities. Special emphasis was placed on gendered identity, along with racial, class, sexual and place-identity as non-discrete categories of identity which nonetheless influence how youth perceive themselves, their peers, and their communities. Adolescents reproduced and resisted popular discourses around violence, gender, and life in working-class communities in South Africa. Youth narrated their understandings and experiences of genderbased and community violence; their efforts to seek safety; their striving for autonomy and achievement; and how they formed different types of relationships as modes of resistance and resilience. This research offered insights that challenged dominant narratives about young people in the Cape Flats, which may inform improved interventions targeted at youth. This study's key contributions included the challenging of binaries of victimisation and perpetration of violence amongst youth, along with those around childhood and adulthood. Preventing youth violence, strengthening buffers to the effects of violence on youth and developing a broader understanding of the underpinnings of violence in working-class communities - particularly sexual and gendered violence - are key areas of research and intervention.